THE USAGE OF TOTAL PHYSICAL RESPONSE METHOD IN TEACHING FOREIGN LANGUAGE IN UZBEKISTAN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the effectiveness of the Total Physical Response (TPR) method in enhancing foreign language learning. By incorporating physical movements into language instruction, TPR helps students enhance vocabulary retention and engagement. The approach reduces stress, increases motivation, and aligns with embodied cognition theories. Findings suggest that movement-based learning strategies make an enjoyable and effective language learning experience, particularly for young learners.